Psychobiological Consequences of Childhood Sexual Abuse: Current Knowledge and Clinical Implications - Lo Iacono, Luisa; Trentini, Cristina; Carola, Valeria (Frontiers in Neuroscience, 2021)
A large body of research has documented the long-term harms of childhood sexual abuse (CSA) on an individual’s emotional-adaptive function and mental health. Recent studies have also provided evidence of the biological impact of CSA, identifying, and implicating specific alterations in many systems, including the endocrine and immune systems, and in DNA and chromatin in the pathogenesis of medical disorders. Although the effects of CSA are often examined with regard to the general impact of early-life traumatic experiences, the study of CSA per sè, as a trigger of specific pathogenic pathways, would be more appropriate to understand their long-term implications and develop tailored diagnostic and therapeutic strategies. Based on these premises, this narrative minireview summarizes the research on the short-term and long-term sequelae of CSA, focusing on dysregulation of the HPA axis, the effects on the immune system, and the changes to DNA through altered methylation. Also, we discuss the literature that examines dysfunctional DNA telomere erosion and oxidative stress markers as a sign of CSA. Finally, recent evidence of the intergenerational transmission of the effects of CSA is reported. The impact of CSA on brain connectivity and functions is out of the scope of this review, thus brain imaging studies are not included. The results of this minireview are discussed, considering their implications for prevention and clinical practice.